Type Checking with XML Schema in XACT - Kirkegaard, Christian; Møller, Anders (BRICS Report Series, 2005)
We show how to extend the program analysis technique used in the XACT system to support XML Schema as type formalism. Moreover, we introduce optional type annotations to improve modularity of the type checking. The resulting system supports a flexible style of programming XML transformations and provides static guarantees of validity of the generated XML data.